2003
DOI: 10.1111/j.1572-0241.2003.08662.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Sertraline As A Treatment for Cholestatic Pruritus in Patients With Primary Biliary Cirrhosis

Abstract: Sertraline use is associated with an improvement in cholestatic pruritus. This novel observation implies that serotonergic fibers are important in regulating the perception of itch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(23 citation statements)
references
References 18 publications
2
18
0
3
Order By: Relevance
“…The selective serotonin uptake inhibitor sertraline (75-100 mg/day) can be administered as fourth-line therapy. A single placebo-controlled crossover trial [94] and a case series [95] reported moderate antipruritic effects. Coadministration of several drugs at the same time is not recommended due to the risk of drug-drug interactions.…”
Section: Managementmentioning
confidence: 99%
“…The selective serotonin uptake inhibitor sertraline (75-100 mg/day) can be administered as fourth-line therapy. A single placebo-controlled crossover trial [94] and a case series [95] reported moderate antipruritic effects. Coadministration of several drugs at the same time is not recommended due to the risk of drug-drug interactions.…”
Section: Managementmentioning
confidence: 99%
“…In a retrospective study of 32 patients with pruritus due to primary biliary cirrhosis (PBC), 4 6 of 7 subjects who had been given sertraline for another indication improved considerably, and pruritus completely disappeared in 3 of those individuals. This pilot study was undertaken to find the optimal dose and to evaluate the safety and feasibility of sertraline as a possible first-line treatment of cholestatic pruritus.…”
mentioning
confidence: 99%
“…4,8 The Browning trial was excluded for two reasons: inadequate patient demographics and retrospective nature of study. 1 Only primary biliary cholangitis (PBC) was included in Browning's study, while PBC, primary sclerosing cholangitis (PSC), and Hepatitis C Virus (HCV) cirrhosis were included in Mayo's study. Therefore, Mayo's study better reflects the breadth of cholestatic disease.…”
Section: Related Literaturementioning
confidence: 99%